2023
DOI: 10.3390/ijms242015259
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Prognosis-Related Genetic Variation in Gastric Cancer Based on mGWAS

Yuling Zhang,
Yanping Lyu,
Liangping Chen
et al.

Abstract: The use of metabolome genome-wide association studies (mGWAS) has been shown to be effective in identifying functional genes in complex diseases. While mGWAS has been applied to biomedical and pharmaceutical studies, its potential in predicting gastric cancer prognosis has yet to be explored. This study aims to address this gap and provide insights into the genetic basis of GC survival, as well as identify vital regulatory pathways in GC cell progression. Genome-wide association analysis of plasma metabolites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…A recent study investigated the genetic variation mechanism of GC prognosis-related metabolites using mGWAS. It detected 32 genetic variant loci that were potentially relevant to GC survival-related metabolites, corresponding to 7 genes, including VENTX , PCDH7 , JAKMIP1 , MIR202HG , MIR378D1 , LINC02472 , and LINC02310 [ 65 ]. In addition, gene oncology (GO) enrichment analysis found that these genes are principally associated with cell signaling molecular transmission, organism growth and development, nervous system regulation, and immune escape-related pathways, suggesting that these functional genes regulate the metabolites via related pathways and thereby affect GC survival.…”
Section: Metabolomics-based Validation Of Predictive and Prognostic M...mentioning
confidence: 99%
“…A recent study investigated the genetic variation mechanism of GC prognosis-related metabolites using mGWAS. It detected 32 genetic variant loci that were potentially relevant to GC survival-related metabolites, corresponding to 7 genes, including VENTX , PCDH7 , JAKMIP1 , MIR202HG , MIR378D1 , LINC02472 , and LINC02310 [ 65 ]. In addition, gene oncology (GO) enrichment analysis found that these genes are principally associated with cell signaling molecular transmission, organism growth and development, nervous system regulation, and immune escape-related pathways, suggesting that these functional genes regulate the metabolites via related pathways and thereby affect GC survival.…”
Section: Metabolomics-based Validation Of Predictive and Prognostic M...mentioning
confidence: 99%